The Effect of Profitability, Dividend Policy, Debt Policy, and Firm Age on Firm Value in The Non-Bank Financial Industry - Vidiyanna Rizal Putri; Arinie Rachmawati (Indonesia Banking School, 2017)
The purpose of this research is to determine the effect of profitability, dividend policy, debt policy, and company age on company value with company size as a control variable. A population of this research is non-bank financial companies listed in Indonesia Stock Exchange (IDX) between 2014-2016. The sampling method that used is purposive sampling method and obtained 38 companies. The independent variable is Return On Equity (ROE) as a measure of profitability, Dividend Payout Ratio (DPR) as a measure of dividend policy, Debt to equity ratio (DER) as a measure of debt policy, and firm age. The dependent variable is Tobins Q as a measure of company value. The control variable is an ln total asset as a measure of firm size. This study uses secondary data that obtained from a financial statement that available on Indonesia Stock Exchange. The results showed that Profitability (ROE), and Debt Policy (DER) have no significant effect, dividend policy has a positive significant effect, and Company age has a negative significant effect on firm value. Meanwhile, the control variable (firm size) have no significant effect on firm value.